Cell specific markers for eosinophils and neutrophils in sputum and bronchoalveolar lavage fluid of patients with respiratory conditions and healthy subjects. Issue 5 (1st May 2002) - Metso, T; Venge, P; Haahtela, T; Peterson, C G B; Sevéus, L
Abstract : Background: Highly specific protein markers for eosinophils and neutrophils could be a valuable diagnostic aid in various respiratory disorders. The cell specificity of monoclonal antibodies against eosinophil peroxidase (EPO), eosinophil cationic protein (ECP), human neutrophil lipocalin (HNL), and myeloperoxidase (MPO) was investigated using immunocytochemical techniques. Methods: Induced sputum and bronchoalveolar lavage fluid samples from 14 patients with respiratory conditions and four healthy individuals were studied. Antigens were detected at their intracellular sites in cells with well preserved structures using optimal techniques for fixation, permeabilisation, and immunolabelling. Results: Anti-EPO antibodies reacted only with eosinophils, and anti-HNL antibodies only with neutrophils. Anti-ECP antibodies reacted with both eosinophils and neutrophils and anti-MPO antibodies with neutrophils and monocytes. Cells not stained by monoclonal anti-EPO and anti-HNL antibodies included lymphocytes, monocytes, macrophages, squamous epithelial cells, and ciliated epithelial cells. Conclusions: EPO, a unique component of eosinophils, and HNL, a unique component of neutrophils, are useful markers for the identification of eosinophils and neutrophils, respectively, in sputum and bronchoalveolar lavage fluid.